Insecticide susceptibility of Anopheles mosquitoes changes in response to variations in the larval environment - Henry F. Owusu (Nature Portfolio, 2017)
Abstract Insecticide resistance threatens the success achieved through vector control in reducing the burden of malaria. An understanding of insecticide resistance mechanisms would help to develop novel tools and strategies to restore the efficacy of insecticides. Although we have substantially improved our understanding of the genetic basis of insecticide resistance over the last decade, we still know little of how environmental variations influence the mosquito phenotype. Here, we measured how variations in larval rearing conditions change the insecticide susceptibility phenotype of adult Anopheles mosquitoes. Anopheles gambiae and A. stephensi larvae were bred under different combinations of temperature, population density and nutrition, and the emerging adults were exposed to permethrin. Mosquitoes bred under different conditions showed considerable changes in mortality rates and body weight, with nutrition being the major factor. Weight is a strong predictor of insecticide susceptibility and bigger mosquitoes are more likely to survive insecticide treatment. The changes can be substantial, such that the same mosquito colony may be considered fully susceptible or highly resistant when judged by World Health Organization discriminatory concentrations. The results shown here emphasise the importance of the environmental background in developing insecticide resistance phenotypes, and caution for the interpretation of data generated by insecticide susceptibility assays.